The Implementation of Metacognitive Strategies in Elementary Mathematics Learning: A Systematic Literature Review - Jauharul Hakim Rizqullah Yeza; Toto Nusantara; Sri Rahayuningsih; Radeni Sukma Indra Dewi; Ratna Ekawati (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: Metacognitive strategies play a critical role in elementary mathematics education by enabling students to plan, monitor, and evaluate their thinking processes. This study conducts a Systematic Literature Review (SLR) to examine the effectiveness of these strategies in enhancing students’ conceptual understanding, motivation, and problem-solving abilities. Using the Publish or Perish application, 432 articles were initially identified from Scopus, Semantic Scholar, and Google Scholar. Based on established inclusion criteria such as publication type, indexing, language, and relevance, 16 studies were selected for in-depth analysis. The findings reveal that metacognitive strategies significantly improve students’ self-regulation, learning independence, and academic performance. However, their effectiveness varies depending on factors such as gender, self-efficacy, classroom environment, and access to technology. The study also highlights the essential role of teachers in modeling cognitive processes, offering feedback, and facilitating reflective learning. Compared to traditional memorization-based instruction, metacognitive approaches foster deeper understanding and cognitive flexibility. This review underscores the need for sustained teacher training and thoughtful technology integration to support effective implementation of metacognitive strategies in primary mathematics learning. Abstrak: Strategi metakognitif memainkan peran penting dalam pendidikan matematika dasar dengan memungkinkan siswa untuk merencanakan, memantau, dan mengevaluasi proses berpikir mereka. Studi ini melakukan tinjauan literatur sistematis (SLR) untuk mengkaji efektivitas strategi-strategi tersebut dalam meningkatkan pemahaman konseptual, motivasi, dan kemampuan pemecahan masalah siswa. Menggunakan aplikasi Publish or Perish, sejumlah 432 artikel diidentifikasi dari Scopus, Semantic Scholar, dan Google Scholar. Berdasarkan kriteria inklusi yang telah ditetapkan, seperti jenis publikasi, pengindeksan, bahasa, dan relevansi, 16 studi dipilih untuk analisis mendalam. Temuan menunjukkan bahwa strategi metakognitif secara signifikan meningkatkan kemampuan regulasi diri, kemandirian belajar, dan prestasi akademik siswa. Namun, efektivitasnya bervariasi tergantung pada faktor-faktor seperti jenis kelamin, kepercayaan diri, lingkungan kelas, dan akses terhadap teknologi. Studi ini juga menyoroti peran penting guru dalam mendemonstrasikan proses kognitif, memberikan umpan balik, dan memfasilitasi pembelajaran reflektif. Dibandingkan dengan pengajaran berbasis hafalan tradisional, pendekatan metakognitif mendorong pemahaman yang lebih dalam dan fleksibilitas kognitif. Tinjauan ini menekankan perlunya pelatihan guru yang berkelanjutan dan integrasi teknologi yang terencana untuk mendukung implementasi efektif strategi metakognitif dalam pembelajaran matematika di tingkat dasar.